Kratek pregled stereotaktičnih radiokirurških tehnik - Velnar, Tomaž (Medicinski razgledi, 2010)
Radiotherapy has long been used in conjunction with classical neurosurgery as a treatment option for benign and malignant tumours, as well as for intracranial lesions. The three possible modalities include fractionated radiotherapy, stereotactic radiotherapy and radiosurgery, the latter employing a gamma knife unit and a linear accelerator system. Radiosurgery is also increasingly applied in combination with systemic therapy for the treatment of metastatic disease.
Keywords: Brain Neoplasms; Možgani, novotvorbe; Radioterapija; Radiotherapy; Stereotaktične metode; Stereotaxic Techniques; Neurosurgical Procedures; Nevrokirurški postopki; Radiokirurgija; Radiosurgery; onkologija; diagnostika; therapy; zdravljenje; gama nož; linearni pospeševalnik